PENGARUH FEE AUDIT, AUDIT TENURE, DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT - Kurnianingsih, Margi; Rohman, Abdul (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to examine the influence of audit fee, audit tenure and audit rotation of audit quality. Audit quality uses proxy size KAP which is measured by dummy variable and using the big four and non big four group of auditors, while tenure is measured by counting the year in which the same auditors has made an engangement with the auditee, audit rotation is measured by dummy variable.The population in this study consists of listed go public firm manufactur in Indonesia Stock Exchange in year 2008-2012. Sampling method used is purposive sampling. In this research, the total of the sample is 645, after data observation then, there are 415 samples that included outlier should be excluded from samples of observation. so, the final amounts of the sample are 230 firms. Logistic regression used to be analysis technique. The empirical result of this study show that audit fee, audit tenure, and audit rotation have significant influenced of audit quality. Audit fee variable positively affects the audit quality, audit tenure negatively affects the audit quality and audit rotation postively affects the audit quality.